Post activation potentiation (PAP) and its application in the development of speed and explosive strength in female soccer players: A review - Pajerska, K.; Zajac, T.; Mostowik, A.; Mrzyglod, S.; Golas, A. (Journal of Human Sport & Exercise, 2021)
The presented review presents the results of current research on the use of PAP during resistance training of soccer players. Researchers who have examined the mechanism behind PAP following complex strength training, have established a relationship between post-activation potentiation and improvements in speed and explosive strength of athletes. Most of the presented papers in this review have confirmed the effectiveness of PAP in eliciting performance in tasks requiring speed, jumping ability and agility in soccer players. These studies were discussed in detail in terms of research groups, methods, training means and study results. Many of these publications have also considered the aspect of rest intervals between the conditioning exercise and the subsequent explosive activity. Most authors indicate the necessity to individualize the time of the rest interval, depending on the athletes training status, strength level and most of all on the intensity and volume of the conditioning exercise. Some scientists have also attempted to incorporate PAP into warm-up protocols, especially prior to speed and power training sessions. A two-way analysis of the impact of PAP, separately on sprint speed and power of the players. The focus was on demonstrating the positive or negative impact of activating exercises on the two variables discussed. The last part of the paper presents the conclusions drawn based on the results of the studies and suggests the objectives of future research. Most publications have documented the results for male participants, whereas little data is available regarding the use of PAP in female soccer players.